Aryl Ketone Mediated Light-Driven Naphthylation of C(sp3)–H Bonds Attached to either Oxygen or Nitrogen Substituents - Azami, Masaya; Murafuji, Toshihiro; Kamijo, Shin (Synthesis, 2022)
A light-driven naphthylation was achieved at C(sp3)–H bonds attached to either oxygen or nitrogen substituents using sulfonylnaphthalenes as a naphthalene precursor in the presence of 4-benzoylpyridine at ambient temperature. The present transformation is proposed to proceed through the generation of a carbon radical species via chemoselective cleavage of the heteroatom-substituted C(sp3)–H bond by photoexcited 4-benzoylpyridine, the addition of the derived carbon radical to the electron-deficient sulfonylnaphthalene, and then rearomatization by releasing sulfinyl radical.
Keywords: C–H functionalization; naphthylation; photoreaction; aryl ketones; ethers; amides